2020
DOI: 10.1136/rapm-2019-101013
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane versus paravertebral nerve blocks for postoperative analgesia after breast surgery: a randomized clinical trial

Abstract: BackgroundParavertebral nerve blocks (PVBs) are frequently used to treat pain during and following breast surgery, but have various undesirable risks such as pneumothorax. The erector spinae plane block (ESPB) also provides perioperative breast analgesia, but is purported to be easier to administer with a favorable safety profile. However, it remains unknown if the new ESPB provides comparable analgesia as the decades-old PVB technique.MethodsSubjects undergoing unilateral or bilateral non-mastectomy breast su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 29 publications
2
79
1
7
Order By: Relevance
“…Swisher et al. [32] reported that the median (IQR) duration of block was 17.7 (9.7–20.1) h for erector spinae plane block vs. 16.0 (11.9–19.9) h for paravertebral block (p = 0.833). Moustafa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Swisher et al. [32] reported that the median (IQR) duration of block was 17.7 (9.7–20.1) h for erector spinae plane block vs. 16.0 (11.9–19.9) h for paravertebral block (p = 0.833). Moustafa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although this concept has changed recently, the fear of hematoma formation with systemic heparinization remains a crucial issue [4,5]. Therefore, the absence of major neurovascular bundles in and around the area of interest renders ESPB safe especially with anticoagulation [14,15]. Despite that, studies investigating the analgesic effect of ESPB in cardiac surgeries with sternotomy are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The results are also similar to those of previous clinical studies showing significantly higher pain scores up to around 6 h after ESPB compared with after TPVB in patients undergoing breast surgery. 11,14 Swisher et al showed that TPVB as compared with ESPB provided superior analgesia and reduced opioid consumption during Post-anesthesia Care Unit (PACU) stay after breast surgery. The median PACU length of stay was 105 min and 124 min in the TPVB and ESPB groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that ESPB was performed in a shorter period of time than TPVB, as previous studies have shown. 14,31 This can be explained by the following two reasons. First, TPVB requires more careful needle handling and advancement of a needle for a longer distance to the target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation